ANALISIS HERMENEUTIKA PEREMPUAN DALAM LAGU RAYUAN PEREMPUAN GILA - Muhammad Farhan; Syafruddin Pohan; Noniya Dewinta; Andre Genesa Harahap (Communicative : Jurnal Dakwah dan Komunikasi, 2023)
The unique and 'wild' lyrical rhetoric loaded and used by Nadin Amizah in the song Rayuan Perempuan Gila seems to create a chain effect that creates a new trend among its listeners. The trend that emerged, where the majority of listeners consciously opened themselves by conveying their shortcomings or declaring themselves as 'crazy women' to their partners or even to the public. Therefore, an analysis of the meaning of the song lyrics was conducted to solve the question "What is the meaning of the rhetoric of the lyrics and how is the representation of women in the song Rayuan Perempuan Gila, Nadin Amizah?" and aims to find out the meaning or rhetoric of the lyrics and the representation of women. The research method used is descriptive qualitative research method, using Paul Ricoeur's hermeneutic approach with explanation and understanding model. Based on the analysis that has been done, it is found that the rhetoric of the lyrics of this song is a manifestation of all the author's worries about her partner's love, the author's sincerity reveals her shortcomings and even the author's courage in representing herself as a crazy woman, the author promises to be a better partner and leave all the bad traits of previous relationships. The results of the analysis of the song lyrics above also show the results that the song Rayuan Perempuan Gila, Nadin Amizah represents women as partners who are full of worries about the failure of past relationships to repeat, want to always be given answers and replies to feelings of love, women who are also figures who also have personalities that can make it difficult for their partners.